Folding DNA into origami nanostructures enhances resistance to ionizing radiation. Issue 25 (18th June 2021) - Sala, Leo; Zerolová, Agnes; Rodriguez, Alvaro; Reimitz, Dan; Davídková, Marie; Ebel, Kenny; Bald, Ilko; Kočišek, Jaroslav
Abstract : The multi-row design of DNA origami structures holds their shape even after severe nicking due to ionizing radiation and their folded structure has a protective effect, i.e., reduced damage compared to free scaffold and similarly sized plasmid DNA. Abstract : We report experimental results on damage induced by ionizing radiation to DNA origami triangles which are commonly used prototypes for scaffolded DNA origami nanostructures. We demonstrate extreme stability of DNA origami upon irradiation, which is caused by (i) the multi-row design holding the shape of the origami even after severe damage to the scaffold DNA and (ii) the reduction of damage to the scaffold DNA due to the protective effect of the folded structure. With respect to damage induced by ionizing radiation, the protective effect of the structure is superior to that of a naturally paired DNA double helix. Present results allow estimating the stability of scaffolded DNA origami nanostructures in applications such as nanotechnology, pharmacy or in singulo molecular studies where they are exposed to ionizing radiation from natural and artificial sources. Additionally, possibilities are opened for scaffolded DNA use in the design of radiation-resistant and radio-sensitive materials.